Italian seismic amplification factors for peak ground acceleration and peak ground velocity. Issue 2 (1st December 2022) - Mendicelli, Amerigo; Falcone, Gaetano; Acunzo, Gianluca; Mori, Federico; Naso, Giuseppe; Peronace, Edoardo; Porchia, Attilio; Romagnoli, Gino; Moscatelli, Massimiliano
ABSTRACT: Ground motion modification over large areas is generally evaluated by focusing on source effects disregarding local lithostratigraphic site conditions. Hence, amplification maps of peak ground acceleration and peak ground velocity are proposed to improve the forecast of ground motion on a national scale. Topological information about litho-type successions and soil mechanical behaviour were retrieved from the Italian database of seismic microzonation and more than 30 million of seismic site response analyses were performed to quantify the amplification factors (i.e. the ratio between expected ground motion at the site of interest and that at the outcropping engineering bedrock). The maximum value of the amplified peak ground acceleration on the Italian territory results in about twice as much as the value expected at the outcropping of the engineering bedrock. Finally, damage scenario maps based on the amplified ground motion could be produced as a supporting tool for urban planning and emergency system management.